Case Report of Polycystic Kidney Disease in a Persian Cat in IPB University Veterinary Teaching Hospital - Budiono, Novericko Ginger; Natawiria, Maria Stella Linda; Rabbani, Syafina Syafaatur; Tuliman, Nurul Annisa; Delimasari, Zahrizada Zamrudina; Rahmiati, Dwi Utari; Fitri, Arni Diana Fitri (Media Kedokteran Hewan, 2024)
A 7-year-old male Persian cat was referred to IPB University Veterinary Teaching Hospital with clinical signs of lethargy, weight loss, and loss of appetite and was diagnosed with nephrolithiasis before being referred to IPB University Veterinary Teaching Hospital. Physical examination revealed tachycardia, tachypnoea, pale mucous membrane, 5–6% dehydration rate, cachexia, and palpated masses on the left and right side of the abdominal region. The abdominal cavity was seen as more radiopaque, which resulted in some organs being invisible in the radiographic view. Abdominal ultrasonography showed abnormalities in the liver, gall bladder, and kidneys. The patient was diagnosed with polycystic kidney disease (PKD) with the prognosis of infausta, as the patient was already in a sternal recumbency and could not stand by himself. During hospitalization, the patient was force-fed with a commercial renal diet, and the medical treatments given were intravenous ceftriaxone, vitamins, furosemide, Azodyl®, and intravenous infusion. The patient regained standing ability and survived until the seventh day of hospitalization. However, the owner persisted in bringing the patient home on the seventh day of hospitalization, and the patient died the next day after being brought home.